Improved extraction of anthocyanins with antibacterial activity from fresh roselle (Hibiscus sabdariffa L.) calyces - Chowdhury, Md Miraj Kobad; Chowdhury, Shibraj; Bari , Latiful; Yeasmin, Sabina (Dhaka University Journal of Biological Sciences, 2024)
Roselle (Hibiscus sabdariffa L.) flower is a commonly consumed vegetable in Bangladesh and have culinary value to preparation of soup, jelly, and baking. Since previous studies suggested the presence of anthocyanins in roselle calyces, this study was designed to enrich anthocyanins from the calyces of this flower. This study explored that addition of mineral acid during the extraction process further enriched the anthocyanins content of the fresh roselle calyces extract. Also, methanol acidified with 1% (v/v) HCl was found as the best solvent to extract anthocyanins from the calyces resulting 7.621±0.001 mg crude anthocyanins per gram of fresh sample. Anthocyanin extraction decreased if 1% (v/v) HCl was replaced with 10% (w/v) tartaric acid or 10% (v/v) acetic acid. The extracted anthocyanins showed minimal antibacterial activity. A further study will explore the possibility of use these anthocyanins for industrial purposes. Dhaka Univ. J. Biol. Sci. 33(2): 139-147, 2024 (July)